Neuroinflammation in Multiple System Atrophy: Response to and Cause of α-Synuclein Aggregation - Vieira, Bruno Di Marco; Radford, Rowan A.; Chung, Roger S.; Guillemin, Gilles J.; Pountney, Dean L. (Frontiers in Cellular Neuroscience, 2015)
Multiple system atrophy (MSA) is a progressive neurodegenerative disease presenting with combinations of autonomic dysfunction, parkinsonism, cerebellar ataxia and/or pyramidal signs. Oligodendroglial cytoplasmic inclusions rich in α-synuclein (α-syn) constitute the disease hallmark, accompanied by neuronal loss and activation of glial cells which indicate neuroinflammation. Recent studies demonstrate that α-syn may be released from degenerating neurons to mediate formation of abnormal inclusion bodies and to induce neuroinflammation which, interestingly, might also favour the formation of intracellular α-syn aggregates as a consequence of cytokine release and the shift to a pro-inflammatory environment. Here we critically review the relationships between α-syn and astrocytic and microglial activation in MSA to explore the potential of therapeutics which target neuroinflammation.